2020
DOI: 10.1007/s13300-020-00813-1
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Sulfonylureas in the Evolving Landscape of Combination Therapy

Abstract: This article summarizes a presentation from a recent symposium entitled ''SUs in the treatment of T2DM: a fresh look and new insights'' held on 18 September 2019 during the 55th Annual Meeting of the European Association for the Study of Diabetes (EASD) in Barcelona, Spain, and discusses whether sulfonylureas (SUs) are a good 'team player.' It examines the likely impact of using SUs early in the course of type 2 diabetes mellitus (T2DM), either alone or in combination with other agents, on glycemic outcomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Other studies showed that the blood level of SU increases in patients with CKD, thereby increasing the risk of developing hypoglycemia when compared with metformin [35]. In contrast, some reports indicate that SU has a strong ability to reduce HbA1c in DM patients [36]. The risk of the cardiovascular or renal event was almost the same in a large cohort of patients (>23,000) taking either SU + metformin or DPP4 inhibitor + metformin.…”
Section: Sulfonylureasmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that the blood level of SU increases in patients with CKD, thereby increasing the risk of developing hypoglycemia when compared with metformin [35]. In contrast, some reports indicate that SU has a strong ability to reduce HbA1c in DM patients [36]. The risk of the cardiovascular or renal event was almost the same in a large cohort of patients (>23,000) taking either SU + metformin or DPP4 inhibitor + metformin.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…glibenclamide, glimepiride) have been a dependable hypoglycemic agent for more than 70 years, several reports have shown that this group of glucose-lowering agent can make cardiovascular events worse [33,34]. Other reports have suggested that SU should be used with care in patients with CKD because blood SU level increases in subjects suffering from CKD [35][36][37][38].…”
Section: Expert Opinionmentioning
confidence: 99%